Experimental implantation of tissue-engineering pancreatic construct - G. N. Skaletskaya; N. N. Skaletskiy; L. A. Kirsanova; G. N. Bubentsova; E. A. Volkova; V. I. Sevastyanov (Вестник трансплантологии и искусственных органов)
Aim: to study the effect of implantation of tissue-engineering pancreatic construct (TEPC) on the course of experimental diabetes mellitus.Materials and methods. The TEPC samples received as a result of joint incubation in vitro floating islet-like cultures (FILC), obtained from the pancreas of newborn rabbits, and the biopolymer microheterogeneous collagen hydrogel (BMCH). Stable diabetes mellitus was caused in Wistar rats by the method of fractional streptozotocin administration.Results. The formation of TEPC occurred at 7-10 days of incubation FILC with BMCH. At the same time, the presence of β-cells with insulin-producing activity was revealed in the TEPC. After intraperitoneal implantation of TEPC samples in rats with streptozotocin diabetes mellitus, there was a significant and persistent decrease in glycemia until the end of the 8-week period of the experiment. Morphological study of pancreas of recipient rats revealed signs of regeneration of own β-cells.Conclusion. The data obtained suggest the combined antidiabetic effect of intraperitoneal injection of TEPC, due to both the direct functioning of the implant and its stimulating effect on the regeneration of β-cells in their own islets of rats with streptozotocin diabetes mellitus.